THE ART-STYLISTIC ROLE OF HUTSUL'S EMBROIDERY IN THE DESIGN OF MODERN WEDDING CLOTHING - Білей-Рубан, Н. В.; Сєдоухова, Є. В.; Петрусь, Л. М. (Art and Design, 2020)
The aim is to study the artistic and compositional characteristics of Hutsul’s ceremonial clothing on the basis of a comprehensive analysis of the decor of the Hutsul wedding dress. In the course of research, the methods of visualization and comparative-historical reconstruction of the national order were used in the analysis of Hutsuls clothing. For the transformation of structural and decorative characteristics into the design principles of modern women's ensembles the method of stylization and the method of combinatorics have been used. The work is based on art analysis and the use of a literary-analytical method to analyze the main information sources. Thanks to the analysis of Hutsul’s ritual clothing in combination with modern technologies of its decoration, the ornamentation on the basis of authentic embroidery of Hutsul region for design ethno-ensembles has been improved. The resulting stylized patterns of embroidery are offered for use in the design of wedding dresses in the ethno style. The methodological basis for the artistic design of the collection of modern ensembles of wedding clothing with ethno-elements is theoretically substantiated and created with the use of the stylization of the main decor. Styled embroideries were developed on the base on the characteristics of Hutsul’s casual clothing as well as a collection of modern wedding dresses in ethnic style was created. The proposed ornamentation of wedding clothing is presented in the design of ethno ensemble, which is useful for experts in the methodology of artistic design of industrial products based on ethno motives.